PARTICULARIZED CONVERSATIONAL IMMPLICATURE IN STAND-UP COMEDY SHOW BY ANTHONY JESELNIK: FIRE IN THE MATERNITY WARD - Abdan Ahadiyat (ReALL - Research on Applied Linguistics and Literature, 2023)
Stand-up comedy and other forms of humor rely significantly on language and the use of words to amuse their audiences. To make humor more subtly funny, comedians frequently use a range of linguistic techniques, such as conversational implicature.  This study investigates the phenomenon of the flouting maxims that raised the particularized conversational implicature in the Netflix stand-up comedy special "Fire in The Maternity Ward" by Anthony Jeselnik. By applying Paul Grice's (1975) theory utilizing the descriptive qualitative method. This study focuses on the strategies to flout the maxims, and the research findings show a total of 86 occurrences of particularized conversational implicatures that are categorized into comprising 39 examples of quality maxims being flouted, including 9 exaggerations, 14 ironies, 2 metaphors, 2 banter, and 12 sarcasms. The flouting of manner maxims is the second most common type, accounting for 28 instances, of which 19 involve vagueness, 7 involve ambiguity, and 2 involve incomplete utterances. The third group, which includes 9 cases of giving hints and 9 instances of presuming, totals 18 instances of flouting relevance maxims. Last but not least, overstating only occasionally results in the quantity maxim being violated. Anthony Jeselnik does not use the following flouting techniques in his stand-up comedy routine: meiosis, understatement, tautology, association clue, over-generalize, and hearer displacement. Ironies and vagueness are the two most used techniques.